2003
DOI: 10.1177/0743558402250345
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Mexican Americans’ Educational Expectations: Longitudinal Effects of Variables Across Adolescence

Abstract: Using a national sample of Mexican Americans, the authors developed structural equation models of the effects of four eighth-grade latent variables on educational expectations assessed 6 years later. Models for Mexican American women and men did not differ from one another. The latent variable, parents’ influences, had a strong positive effect on educational expectations at late adolescence. Parents’ influences dominated the effects of the other latent independent variables, socioeconomic status, eighth-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 31 publications
4
41
0
2
Order By: Relevance
“…Both fall under the category 'informal parent involvement' as discussed by LeFevre and Shaw (2012). This theme also ties into the studies by Rodriguez (2002) and Trusty et al (2003), which showed a positive relationship between parents' encouragement and their children's school results.…”
Section: Creating a Supportive Home Environmentmentioning
confidence: 79%
“…Both fall under the category 'informal parent involvement' as discussed by LeFevre and Shaw (2012). This theme also ties into the studies by Rodriguez (2002) and Trusty et al (2003), which showed a positive relationship between parents' encouragement and their children's school results.…”
Section: Creating a Supportive Home Environmentmentioning
confidence: 79%
“…This motivational function of parental expectations is supported by eight articles demonstrating a strong association between parental expectations and students' expectations or aspirations (Benner and Mistry 2007;Beutel and Anderson 2008;Carpenter 2008;Hao and Bonstead-Burns 1998;Rutchick et al 2009;Smith-Maddox 2000;Trusty 2002;Trusty et al 2003). A recent longitudinal study of 884 children aged 6 to 13 years when the study began demonstrated the long-lasting effect of parental expectations on children's expectations.…”
Section: High Parental Expectations Indicate That Parents Value Achiementioning
confidence: 89%
“…While most of the research conducted to date has been cross-sectional, a few longitudinal studies offer particularly powerful evidence that parental expectations are a causal determinant of student expectations and academic outcomes (Rutchick et al 2009;Trusty et al 2003). Additionally, two meta-analyses have found that parental expectations are the strongest family-level predictor of student achievement outcomes, exceeding the variance accounted for by other parental beliefs and behaviors by a substantial margin (Jeynes 2005(Jeynes , 2007.…”
mentioning
confidence: 99%
“…Apoyo parental y autoconcepto filial producirían mayor rendimiento académico, que a su vez los reforzaría. Muchas investigaciones confirmaron la fuerte relación entre expectativas parentales y autoconcepto y expectativas filiales (Neuenschwander, Vida, Garrett y Eccles, 2007;Rutchick, Smyth, Lopoo y Dusek, 2009;Seginer, 1983;Yamamoto y Holloway, 2010;Trusty, Plata y Salazar, 2003). La relación entre expectativas y apoyo parentales es mucho más discutida (Hughes et al, 2013).…”
Section: Las Expectativas Como Indicador De La Ambición De Logrounclassified
“…La relación entre expectativas y apoyo parentales es mucho más discutida (Hughes et al, 2013). Mientras algunos estudios encuentran relación entre ambas (Rutchick et al, 2009), otros no hallan relación significativa (Englund, Luckner, Whaley y Egeland, 2004;Trusty, et al, 2003). Esas discrepancias pueden deberse a diferencias metodológicas, especialmente a la diversidad de formas de medir la implicación parental (Yamamoto y Holloway, 2010;Fan, 2001), así como al hecho de que en muchos casos la mayor implicación puede ser una respuesta a problemas escolares (Lee y Bowen, 2006).…”
Section: Las Expectativas Como Indicador De La Ambición De Logrounclassified